Multiple sclerosis: overview of orally administrated disease-modifying drugs. Do genetics influence the success of treatment? - Ovčinikova , A.; Kizlaitienė , R. (Neurologijos seminarai, 2019)
Multiple sclerosis (MS) is the main cause of acquired neurological disability in the young people. In MS treatment, disease modifying therapies (DMTs) are essential to reduce disease progression by suppressing the inflammatory response responsible for promoting lesion formation. Injectable (Interferons and Glatiramer acetate) and infusion (Natalizumab, Alemtuzumab) therapies are both effective however rather exhausting for patients. Recently, in addition to the injectable and infusion DMTs, new orally administered drugs have been approved for MS therapy: fingolimode, dimethyl fumarate, and teriflunomide. These drugs act with different mechanisms on the immune system and are more comfortable for MS patients. In this review we provide a systematic description of the new oral drugs fingolimod, dimethyl fumarate and teriflunomide and also introduce the influence of polymorphic gene variants in the Human Leukocyte Antigen region on the risk of developing MS and its progression and effectiveness of DMTs.
Keywords: multiple sclerosis; orally administrated drugs; fingolimod; dimethyl fumarate; teriflunamide; human leukocite antigen